Depression and the ischemic heart disease - Opielak, Grzegorz; Tsyganok, Mykola; Piotrkowicz, Jakub; Szeszko, Łukasz; Maciejewski, Ryszard; Dworzański, Wojciech (Polish Journal of Public Health, 2013)
Depression and coronary heart disease are more and more frequently co-occurring illnesses. It is noticed that individuals falling to the severe episode of the ischemic heart disease are more often struck by depression. Individuals, at whom disorders appeared with the depressive background, present an increased risk of the ischemic heart disease development. An inherent prognostic element in the course of cardio-vascular illnesses is a mental state of the sick person. The key element of prevention and curing in cardio-vascular illnesses is an appropriate contact, full understanding of the problem of the ischemic heart disease, which in the course of depression are made difficult.